Agricultural water management in a water stressed catchment: lessons from the RIPARWIN Project - McCartney, Matthew P.; Lankford, B.A.; Mahoo, H.F. (International Water Management Institute, 2007)
In the face of growing water stress and increasing concerns over the sustainability of water use, Tanzania has, in common with many other countries in Africa, focused largely on the development of more integrated catchment-wide approaches to water management. In the Great Ruaha River Basin, considerable effort has gone into increasing water productivity and the promotion of mechanisms for more efficient allocation of water resources. Over a period of five years, the RIPARWIN project investigated water management in the basin and evaluated the effectiveness of some of the mechanisms that have been introduced. The study findings are relevant to basins in developing countries where there is competition for water and irrigation is one of the main uses.